2018
DOI: 10.14419/ijet.v7i3.13.16339
|View full text |Cite
|
Sign up to set email alerts
|

Academic Social Network Sites: Opportunities and Challenges

Abstract: Academic Social Networking Sites (ASNs) have become one of the most important platforms in modern information and education industries. It will definitely become an essential mechanism to communicate, connect and collaborate among the scholarly community. In this paper, we provide a comprehensive investigation of ASNs such as Academia, ResearchGate, Mendeley and Zotero, and identify the features of ASNs. We also discuss the opportunities for ASNs and provide the challenges. Challenges related to ASNs are: coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Due to the inherent social network generated from academic activities (such as citations, collaborations, and academic communications)—named academic social network (Mohamad, Lazim, & Rosle, 2018), social network analysis has been proposed to investigate the topologies and dynamics of this network (Xia et al, 2017). Social network analysis is mainly based on the graph theory (Deo, 1974) and aims to describe, analyze, and simulate an academic social network by representing, visualizing and detecting communities in a given network of main scientific entities such as researchers, papers, conferences, and citations.…”
Section: Scholarly Data Mining Methodsmentioning
confidence: 99%
“…Due to the inherent social network generated from academic activities (such as citations, collaborations, and academic communications)—named academic social network (Mohamad, Lazim, & Rosle, 2018), social network analysis has been proposed to investigate the topologies and dynamics of this network (Xia et al, 2017). Social network analysis is mainly based on the graph theory (Deo, 1974) and aims to describe, analyze, and simulate an academic social network by representing, visualizing and detecting communities in a given network of main scientific entities such as researchers, papers, conferences, and citations.…”
Section: Scholarly Data Mining Methodsmentioning
confidence: 99%
“…The intensity of mutual suppression of circulation increases with increasing number of interacting layers. The azimuthal velocity profiles presented in [19], obtained by calculation for the value of Reynolds numbers Re = 500 (laminar flow) have a similar appearance. However, since the flow regime is laminar, the process of viscous diffusion of circulation of the interacting layers terminates here at the 40th radius of the interaction area.…”
mentioning
confidence: 62%
“…A total of 17 studies are incorporated under this theme. These studies primarily investigated the feature and services of RG, (Bhardwaj, 2017;Chen et al, 2018;Copiello & Bonifaci, 2018Mohammad et al, 2018;Ortega, 2017) Academia.edu, Mendeley, and Zotero, (Bhardwaj, 2017;Mohammad et al, 2018;Sugimoto et al, 2017) General ASNs (Jordan, 2018;Laakso et al, 2017;Radford et al, 2018;Sugimoto et al, 2017).…”
Section: Asn Features and Services (Theme Iii)mentioning
confidence: 99%
“…Examining ASN features and services may also help to understand the user's perceived acceptance, usefulness, as well as the reliability of these services. Mohammad et al (2018) evaluated the features and services of RG, Academia.edu, Mendeley, and Zotero. The study found that the highest percentage of page views per user was observed in RG and Academia.edu.…”
Section: Asn Features and Services (Theme Iii)mentioning
confidence: 99%